Resposta :
Resposta:
1.
a) (-4)²-(-2)³= (-4.(-4)) - (-2.(-2).(-2)) = 16+8 = 24
b) (-3)²-5= 9-5= (-3x(-3)) - 5 = 9 - 5 = 4
c) (-3)-5.(-2)= -3 - (-10) = -3 + 10 = 7
d) (-4)²-(-2)³= (-4.(-4)) - (-2.(-2).(-2)) = 8 + 8 = 16
2.
a) 2 + 2 = 4
b) 2.2 + 10 = 4 + 10 = 14
c) 2² - 12 = 2.2 - 12 = 4 - 12 = -8
d) 2² + (2.2) = 2.2 + 4 = 4 + 4 = 8
3. É só substituir os valores das variáveis (letras)!
a) a - b, quando a = -3 e b= -2
a - b = -3 - (-2) = -3 +2 = -1
b) x² - 6x, quando x = -4
(-4)² - 6.(-4) = (-4.(-4)) - 24 = 16 - 24 = -8
c) 2x - 7y, quando x=+2 e y= -3
2x - 7y = 2.(2) - 7.(-3) = 4 - ( -21) = 4 +21 = 25